Health care and human vulnerability: A Confucian perspective - Chan, Jonathan (Studia Bioethica, 2012)
It is widely accepted that we bear special responsibilities to those who are vulnerable, especially those who are vulnerable to our actions and choices. However, exactly who fall under the category of the vulnerable? What special responsibilities do we have toward them? And on what ground? These are the main questions this paper attempts to address. The question of who fall under the category of the vulnerable is a conceptual one. A satisfactory account of the category in question requires not only that we should be able to describe the extension of the ‘vulnerable’ but also that we are able to provide some reasons for ascribing vulnerability. Otherwise, ‘vulnerability’ functions no more than a label. However, why should we care about vulnerability? Why should we care about vulnerable people? Some might say that we should care about them because justice requires us to do so. In what follows, however, I shall argue that justice cannot fully account for the widely held moral intuition that we have special responsibilities to the vulnerable people, and that the Confucian provides a better explanation for that intuition. The paper also will discuss the moral position of the Confucian perspective on our moral responsibilities to the vulnerable groups in the context of health care. The discussion will reference to the Universal Declaration on Bioethics and Human Rights adopted by the General Conference of UNESCO in 2005.